2020
DOI: 10.1101/2020.03.18.997031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic switching between intrinsic and extrinsic mode networks as demands change from passive to active processing

Abstract: We here report on the relationship between default and extrinsic mode networks across alternating brief periods of rest and active task processing. We used three different visual tasks: mental rotation, working memory and mental arithmetic in a classic fMRI ON-OFF block design where task (ON) blocks alternated with equal periods of rest (OFF) blocks. By analysing data in two ways, using an ON-OFF contrast, we showed the existence of a generalized task-positive network, labelled the extrinsic mode network (EMN)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This stark synaptic connectivity contrast between ilPFC- and plPFC-driving circuits, may suggest that the claustrum supports discrete network states. Considering that human task-positive and task-negative cortical networks are anti-correlated (Fox et al, 2005; Uddin et al, 2009; Riemer et al, 2020), and that ilPFC and RSC are identified as two major putative nodes of the default mode network in mouse (Stafford et al, 2014), whereas the plPFC and PtA are putative mouse homologs of major nodes in the human fronto-parietal network (Hwang, 2021; Laubach et al, 2018), the present data may support the idea of the claustrum acting as a relay system sculpting defined cortical networks.…”
Section: Discussionmentioning
confidence: 99%
“…This stark synaptic connectivity contrast between ilPFC- and plPFC-driving circuits, may suggest that the claustrum supports discrete network states. Considering that human task-positive and task-negative cortical networks are anti-correlated (Fox et al, 2005; Uddin et al, 2009; Riemer et al, 2020), and that ilPFC and RSC are identified as two major putative nodes of the default mode network in mouse (Stafford et al, 2014), whereas the plPFC and PtA are putative mouse homologs of major nodes in the human fronto-parietal network (Hwang, 2021; Laubach et al, 2018), the present data may support the idea of the claustrum acting as a relay system sculpting defined cortical networks.…”
Section: Discussionmentioning
confidence: 99%